Cross-sectional interview-based study on profile of menstrual cycles and menstrual hygiene among undergraduate medical students in a metropolitan city - Pokle, Sanhita Shyam; Malgaonkar, Aniruddha Arjun; Kartikeyan, Sundaram (International Journal of Research in Medical Sciences, 2016)
Background: Taboos, socio-cultural restrictions, misconceptions and unhygienic practices associated with menstruation may cause adverse health outcomes. The mode of imparting information about menstruation may influence a girl’s beliefs and attitude towards menstruation in later years. Aims and Objectives of the study were to assess the profile of menstrual cycles and menstrual hygiene among undergraduate medical students. Methods: After obtaining requisite permissions and explaining the purpose of the study, written informed consent was obtained from willing participants. All participants were interviewed by the same female investigator using a pre-tested semi-structured questionnaire and the responses were statistically analyzed. Results: The age at menarche ranged from 9-16 years (median=13 years). During menarche, the primary sources of information were mothers, teachers and elder sisters for 89.15% respondents. The mean duration of menstrual bleeding was 4.74 days (SD=1.11 days). Peri-menstrual symptoms included fatigue, craving for certain foods, breast tenderness and mental irritability. Those with irregular menses had higher likelihood (OR=2.567) of experiencing heavy menstrual bleeding. 59.09% resorted to self-medication. The frequency of changing sanitary pads and cleaning genital area during menses was inadequate in many respondents. Conclusions: Despite being medical students, many resorted to self-medication for menstrual problems and had inadequate menstrual hygiene.